Analysis of Factors Affecting the Quality of Corn and the Supply Chain as An Animal Feed Ingredient in Karo District, North Sumatra - Joko Susilo; Ma’ruf Tafsin; Elisa Julianti (Randwick International of Social Science Journal, 2024)
This study aims determine the quality of corn, analyze the factors that influence corn quality and analyze differences in corn prices at the farmer and marketing level in Karo Regency. This research was carried out in Karo Regency in May - July 2023 with a total of 98 respondents. It used multiple linear analysis. The results of the research show that the quality of corn available to farmers and marketing meets SNI requirements as raw material for animal feed. The results of multiple regression analysis show that water content, supply chain and harvest season have a significant effect on corn quality in Karo Regency. The marketing margin for farmers is as high as IDR 523/kg, while at marketing level it is IDR 1,012/kg. The farmer share obtained at farmer level was 89.24%, while at marketing level it was 82.71%.